CONVERSATIONS AMONG FRIENDS: REFLECTING GENDER SOCIAL NORMS - Gаlynа Tsapro Tetiana Kychan (Studia Philologica, 2017)
The article studies gender differences in speech in the sitcom series “Friends”. The research focuses on the topic choice made by characters. The dialogue discourse under study is interpreted and subdivided into minimal conversational fragments. The conversation topics are considered in three groups: conversation between two female friends, conversations between two male friends and conversation in the mixed sex group. To study gender peculiarities of the conversation among friends the following methods have been applied: discourse analysis, context-interpretation analysis and conversational analysis — the combination of these analyses is used to study the dialogue discourse with the aim to select, mark and separate minimal dialogue fragments for further gender topic research; comparative method is used to compare topics in three groups of characters: F-F (homogender conversation between women), M-M (homogender conversation between men), M-F (heterogender conversation between a man and a woman). Television series are marked by a number of particular features: regularity of broadcasting, stable plot unfolding, length, recurrence of some plot lines. Furthermore, series are in an advantageous position if compared with any other television product due to their unique relations with the viewers. Television series are considered to be an impactful instrument of reaching the audience and one of the primary sources of giving information to those who watch. Being the mass culture outcome, series express the spirit of the contemporary society, have enormous ability to effect emotional reaction and simultaneously and to moderate (weaken, reduce) rational perception of the reality. Moreover, series create the peculiar picture of the world which is immensely different from everyday routine life. Besides, due to series the audience is given some new experience. Furthermore, present-day films focus on the future norms of the society more than reflecting the past ones; they create and introduce new vision of social norms and stereotypes. Gender is studied as a set of physical, psychological, behavioural features that are expected from the corresponding gender in the society, in other words it is the blending, mixture or cooperation of sex and social status of a personality. The sitcom “Friends” has created a particular image about young people’s life implying clearly that women might be seeking more independence than it is usually depicted in fiction stories and movies. The series has been forming a public perception of friendship in the modern society stressing the fact that friendship is possible not only between friends of the same sex but of the opposite as well. This idea is rather revolutionary. In huge megalopolises when people feel more and more lonely the idea of someone you can talk to, someone you can share your feelings with and simply spend time and talk about whatever is supported and developed in the series. The idea is that you can make friends and enjoy relationships not only with the friends of the same sex. Recent research on everyday dialogues has revealed that five broad topic areas can be identified: people and relationships, work and money, leisure activity, appearances and personal traits of character, and social issues such as current events, politics, sport. Social roles in films may accentuate dynamics of changes in the society. Generally, according to social stereotypical patterns, girls should be taught to wash clothes, to separate clothes, to be aware of similar things On the contrary, in the series “Friends” male character Ross teaches his female friend Rachel how to deal with her clothes. It creates a certain comic effect in the scene. On the other hand, it reflects possible true-to-life situations and in its turn makes the audience accept the new variant of social roles when young men do know how to do the chores and young girls have no idea about it. Analyzing conversation discourse of the series “Friends”, 81 fragments of minimal dialogue part have been singled out for the study: 36 fragments of conversation between female friends, 15 fragments between male friends and 30 fragments between a male friend and a female friend. 112 Філологічні студії The topic variation is presented with the biggest proportion of talks about people and relationships: 63.9 % of all conversations between female friends, 73.3 % between male friends and 66.7 % between a male friend and a female friend. Topic choice in the comedy mostly concerns relationships. Topic choice suggested in comedies mainly concerns relationships. The explanation is determined by the aim of the series to entertain the audience instead of speaking about job or money problems. The aim of the further research is studying gender conversational topics in series demonstrating friendship of middle aged generation representatives paying attention to the sitcoms made in Ukraine which will enable the researchers to make a comparative analysis of gender topic choices in different cultures.